Beam Synthesis with Low-Bit Reflective Coding Metamaterial Antenna: Theoretical and Experimental Results - Qinhao Wu; Yongqiang Cheng; Xiang Li; Hongqiang Wang (International Journal of Antennas and Propagation)
Coding metamaterials are the new technology where the aperture coding provides the hardware foundation for the miniaturization of the devices. As a synthetic 2-D plane, metamaterial antennas are composed of subwavelength resonant particles. It can realize real-time control of electromagnetic wave and build multifunction radar array system. We make a detailed explanation of its array structure, working principle, and hardware system. However, it is usually difficult to synthesize flexible beams because the phase value is very limited in this antenna. Two methods are proposed in this paper to demonstrate the beam synthesis based on repetitive coding and convolution, and the distribution of beam pointings is analysed on the basis of this mechanism. Experiments that measure the radiation pattern of this antenna are carried out to verify the simulated results using only 1-bit coding metasurface in a radar system, whose phase value is controlled by pin diode on the surface.